2015
DOI: 10.1002/jat.3150
|View full text |Cite
|
Sign up to set email alerts
|

Titanium dioxide nanoparticles increase plasma glucose via reactive oxygen species‐induced insulin resistance in mice

Abstract: There have been few reports about the possible toxic effects of titanium dioxide (TiO2 ) nanoparticles on the endocrine system. We explored the endocrine effects of oral administration to mice of anatase TiO2 nanoparticles (0, 64 and 320 mg kg(-1) body weight per day to control, low-dose and high-dose groups, respectively, 7 days per week for 14 weeks). TiO2 nanoparticles were characterized by scanning and transmission electron microscopy (TEM) and dynamic light scattering (DLS), and their physiological distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 30 publications
4
38
0
1
Order By: Relevance
“…The TOS levels in TiO 2 -exposed rats were also increased in the present study, but this was not statistically significant. In recent years, there has been considerable evidence in the literature on ROS increase and antioxidant system failure following TiO 2 , CuO, ZnO, and Al 2 O 3 exposures of rats (Sha et al, 2011;Yu et al, 2014;Hu et al, 2015;Lei et al, 2015), supporting the present data, which showed the TOS increase in the serum.…”
Section: Total Oxidant and Antioxidant Statussupporting
confidence: 90%
“…The TOS levels in TiO 2 -exposed rats were also increased in the present study, but this was not statistically significant. In recent years, there has been considerable evidence in the literature on ROS increase and antioxidant system failure following TiO 2 , CuO, ZnO, and Al 2 O 3 exposures of rats (Sha et al, 2011;Yu et al, 2014;Hu et al, 2015;Lei et al, 2015), supporting the present data, which showed the TOS increase in the serum.…”
Section: Total Oxidant and Antioxidant Statussupporting
confidence: 90%
“…A theoretical framework study comparing redox potentials of the relevant intracellular reactions with NP energy band structure showed that harmful oxide NPs possess band energy levels comparable to redox potentials of these biological reactions, leading to generation of ROS . Earlier research by our group focusing on the toxic effects of TiO 2 NPs on the endocrine system in mice demonstrated that oral administration of these NPs leads to increased plasma glucose levels . Moreover, generation of ROS appeared to be the predominant mechanism underlying the TiO 2 NP‐mediated increase in plasma glucose and consequent toxic effects .…”
Section: Introductionmentioning
confidence: 97%
“…8 Earlier research by our group focusing on the toxic effects of TiO 2 NPs on the endocrine system in mice demonstrated that oral administration of these NPs leads to increased plasma glucose levels. 9,10 Moreover, generation of ROS appeared to be the predominant mechanism underlying the TiO 2 NP-mediated increase in plasma glucose and consequent toxic effects. 10 Notably, inhibition of ROS in TiO 2 NP-treated mice with resveratrol (Res) and vitamin E (Ve) resulted in suppression of plasma glucose levels in mice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent studies suggest that it also poses adverse biological and environmental toxicity depending on the size, surface area, charge and media interactions (Donaldson et al, 2001;Nel et al, 2006;Oberdoester, 2010;Oberdorster et al, 2005). The potential of TiO 2 in the production of reactive oxygen species (ROS) and proinflammatory responses in cells were reported earlier (Hu et al, 2015;Meena et al, 2015). They are also found to cause a neurological lesion Ze et al, 2014).…”
Section: Introductionmentioning
confidence: 99%